The prescription practices of adrenaline auto-injector for children at risk of anaphylaxis - Elghoudi, Ahmed; Stiefel, Gary; Holloway, Judith (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Background: Guidelines on indications for adrenaline auto-injector (AAI) exist. There is no consensus on the prescription criteria of AAI. However, the European Academy of Allergy and Clinical Immunology (EAACI) and the United Kingdom (UK) resuscitation council provide guidances on prescription practices. Objectives: This study aims to investigate prescription practices of AAIs prescribed by members of four regional pediatric allergy groups (PAGs) in the UK. Materials and Methods: An online questionnaire was e-mailed to the PAGs members. Scenarios of absolute and relative indications for AAI prescriptions (as per the EAACI guidelines) were presented to clinicians to establish whether they would prescribe an AAI. Results: One hundred and seventeen responses from members of PAGs working in four different regions were received. Practices were similar in scenarios of absolute indications for AAI. Intraregional (variations within the regions) as well as interregional (variations between the regions) variations were observed. There were statistically significant interregional differences in scenarios of relative indications for AAIs. For mild reaction to peanut (PN)/tree nut (TN), AAI would be prescribed more often by doctors from Wessex clinicians (67%) than those from Midlands (31%), London (24%), and Northern (20%) (P < 0.05). Whereas for a previous mild reaction to trace of PN/TN, Northern clinicians (47%) would prescribe AAI less often than those from the Midlands (78%), Wessex (82%) and London (79%) (P < 0.05). Intraregional differences were also observed. Conclusions: There is a consensus with absolute indications for AAI prescriptions across and within regions. There are intraregional and interregional differences in prescribing practices in scenarios where there is a relative indications for an AAI. Better intra- and interregional work could improve consistency or practice across the country are explain differences in practice.
Keywords: Adrenaline auto-injector/adrenaline auto-injectors; allergy; generalized hives and lips swelling; mild allergy; peanut; tree nuts